Developing EFL Students’ Metacognition by Using Question – Answer Relationship (QAR) Strategy - Yahya, Nagham Qadoori; Kareem, Moayad Yahia (Journal of Tikrit University for Humanities, 2021)
Language is at the heart of human life, serving as a conduit for the exchange of ideas, interactions, and the formation of social and individual identities. Reading is one of the most critical language skills to teach. It is a fluent process in which a person combines information from a text with their own prior knowledge to create meaning. Developing metacognitive processes is a crucial subject and it is highly beneficial to language learning. The current study aims at demonstrating the effect of Question-Answer Relationships (QAR) strategy in developing students’ metacognition with regard to reading comprehension.This study mainly aims at finding out: 1.The degree to which the students' metacognitive abilities in relation to their linguistic repertoire have developed. The extent to which EFL students have developed their metacognitive skills through reading comprehension by using question-answer relationship (QAR). These requirements were achieved by confirming the following hypothesis: There is no statistically significant difference between the mean scores of the experimental group's achievement and that of the control group in the posttest applying question-answer relationship (QAR) on the reading comprehension. To verify the hypothesis of the study, a sample of 50 students have been randomly selected from the fifth preparatory grade at Al Dour Preparatory School for Boys .The sample was split into two groups: one for the experiment and the other for the control. Both of these groups are comparable in terms of their previous year's English language scores, age, and parent's educational level. The researcher used an achievement test is constructed and applied to asses evaluate the students' success in the study's dependent variable. The study lasted ten weeks. Results of this study revealed that there was a statistically significant difference between the mean scores of the EG and that of the CG in the reading comprehension achievement post test ,i.e. the scores of the students in reading comprehension in the EG was significantly higher in average than that of the students in the CG on the post test . As a result, the current study's findings verified the importance of Question Answer Relationship (QAR) in improving students' metacognition with regard to reading comprehension skills. Finally, the study ended with some conclusions and recommendations.